2007
DOI: 10.1158/0008-5472.can-06-3724
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Inhibits p53-Mediated Transcriptional Repression: Implications for the Regulation of Apoptosis

Abstract: Estrogen receptor A (ERA) and tumor suppressor protein p53 exert opposing effects on cellular proliferation. As a transcriptional regulator, p53 is capable of activating or repressing various target genes. We have previously reported that ERA binds directly to p53, leading to down-regulation of transcriptional activation by p53. In addition to transcriptional activation, transcriptional repression of a subset of target genes by p53 plays important roles in diverse biological processes, such as apoptosis. Here,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
126
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 47 publications
6
126
1
1
Order By: Relevance
“…One such modulator of p53 signaling is ERα. We have reported that in ER-positive human breast cancer cells, as well as in a mouse xenograft model, ERα binds to p53 and represses its transcriptional function (13)(14)(15), resulting in inhibition of p53-mediated cell cycle arrest (14) and apoptosis (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One such modulator of p53 signaling is ERα. We have reported that in ER-positive human breast cancer cells, as well as in a mouse xenograft model, ERα binds to p53 and represses its transcriptional function (13)(14)(15), resulting in inhibition of p53-mediated cell cycle arrest (14) and apoptosis (15).…”
mentioning
confidence: 99%
“…We provide evidence that ERα recruits corepressors when bound to p53 and show that the ERα-p53 interaction is relevant to normal mammary stem cell regulation and to breast cancer patient response to antiestrogen therapy. We have previously demonstrated that ERα binds to p53, leading to functional repression of p53 transcriptional activity (13)(14)(15). To explore the mechanisms by which ERα inhibits p53-mediated transcriptional activation of the p21 gene, a prototypic p53-target gene, we performed conventional and sequential site-specific ChIP assays to analyze whether ERα recruits corepressors to the p53-binding site of the p21 promoter.…”
mentioning
confidence: 99%
“…In our EL and LMWEs overexpressing clones, Bax expression has remained unchanged and Bcl-2 expression has been upregulated ( Figure 4b). It is known that ER can directly bind p53 and suppress p53 mediated transcription including Bax (Roemer and Friedmann, 1993;Liu et al, 2006;Sayeed et al, 2007). Therefore, lack of Bax down regulation in presence of high p53 content, induced by cyclin E, can be related to elevated ER.…”
Section: Discussionmentioning
confidence: 99%
“…While ERs are master regulators essential for development and maintenance of normal sexual and reproductive functions, they can also play a role in the cardiovascular, musculoskeletal, immune and central nervous systems. [8][9][10] These two diverse networks exhibit crosstalk that can be due to direct interaction between p53 and the ERs, with the more frequently described outcome being repression of p53 activity, [11][12][13][14] although p53 can also inhibit ERα. 15,16 The inhibitory crosstalk, which can be mediated by physical interactions between the two proteins, can be relieved by stress-dependent post-translational modifications of p53.…”
Section: Interaction Between P53 and Estradiol Pathways In Transcriptmentioning
confidence: 99%
“…15,16 The inhibitory crosstalk, which can be mediated by physical interactions between the two proteins, can be relieved by stress-dependent post-translational modifications of p53. 12,14 The p53/ER interactions can also result in mutual positive regulation at the level of target gene expression level. 17,18 Most of the studies addressing p53/ER interaction were performed in breast cancer cell lines, implicating regulation of the activity and expression of p53 and ERs in tumorigenesis.…”
Section: Interaction Between P53 and Estradiol Pathways In Transcriptmentioning
confidence: 99%